Governance of the Food System in the Mekong Delta, Cambodia: Rice, Fish, Water and NRM - Sithirith, Mak; Sok, Sao; De Silva, Sanjiv; Kong, Heng; Kongkroy, Chay; Thavrin, Tim; Sarun, Hy (WorldFish, 2023)
River, lake, floodplains and farmland produce foods to sustain livelihoods of communities for many generations. Given the increased population and development needs, these food production land-waterscapes have been so-called developed and transformed into specialized and controlled landscapes, claiming at increasing the management and improved productivities. These have induced the disconnection between rivers, floodplains, lakes and farmlands. Policy and institutional frameworks have been attached to these land-waterscapes. Irrigation systems have been built, cutting across the rivers, floodplains and landscapes and claiming to provide water to irrigate and improve rice farming across countries. Fishery domain has been managed into CFis and CFRs, claiming to protect and conserve fish for foods for rural population who live dependent on these resources for generations. However, fishery resources have affected by the irrigation development and rice farming, leading to decline in fish production.